Workshop Penyusunan Instrumen Literasi Statistik bagi Calon Guru Berbasis Konteks Perubahan Iklim - Drajat Friansah; Ratu Ilma Indra Putri; Yusuf Hartono; Somakim Somakim (JURNAL CEMERLANG: Pengabdian pada Masyarakat, 2025)
The low level of statistical literacy among teachers and pre-service teachers poses a significant challenge to the implementation of the Merdeka Curriculum and the Minimum Competency Assessment (AKM). This community engagement activity aims to enhance statistical literacy through a workshop that integrates the issue of climate change. The workshop methodology involves conceptual sessions, practical instrument development, and evaluation through pretest and posttest. The integration of actual data from the Meteorological, Climatological, and Geophysical Agency (BMKG) and the application of the Indonesian Realistic Mathematics Education (PMRI) approach are key elements of the methodology. Evaluation results indicate a significant improvement in participants' understanding of statistical concepts and their ability to develop contextual assessment instruments. This approach has also proven effective in fostering critical awareness and data-based thinking skills. The workshop serves as a strategic step in strengthening statistical competencies among teachers and pre-service teachers, which is essential for building a solid foundation of data literacy in educational settings.